Effect of alemtuzumab over sNfL and sGFAP levels in multiple sclerosis - Sainz-Amo, Raquel; Rodero Romero, Alexander; Monreal, Enric; Chico García, Juan Luis; Fernández Velasco, José Ignacio; Villarrubia, Noelia; Veiga González, Jose Luis; Sainz de la Maza, Susana; Rodríguez Jorge, Fernando; Masjuan, Jaime; Costa-Frossard, Lucienne; Villar, Luisa María (Frontiers in Immunology, 2024)
Introduction: Alemtuzumab is a highly effective pulsed immune reconstitution therapy for multiple sclerosis (MS). Aim: To evaluate serum neurofilament light chain (sNfL) and serum glial fibrillary acidic protein (sGFAP) in patients with relapsing-remitting MS who have been treated with Alemtuzumab over the course of 2 years. Methods: This prospective study involved MS patients treated with Alemtuzumab at a referral MS center. Both sNfL and sGFAP were analyzed at baseline and then again at 6, 12, and 24 months post-treatment using the single molecule array (SiMoA) technique.We also recruited matched healthy controls (HCs) for comparison.The study included 46 patients (with a median age of 34.2 [Interquartile range (IQR), 28.7-42.3] years, 27 of which were women [58%]) and 76 HCs. No differences in demographic characteristics were observed between patients and HC. The median disease duration was 6.22 (IQR, 1.56-10.13) years. The median annualized relapse rate before treatment was 2 (IQR, 1-3). At baseline, sNfL and sGFAP levels were higher in MS patients (median of 18.